Alternaria leaf blight of clusterbean - Е. Е. Radchenko; R. A. Abdullaev; N. V. Alpatieva; O. V. Putina; E. L. Gasich (Вавиловский журнал генетики и селекции)
The annual  legume  crop clusterbean (Cyamopsis tetragonoloba  (L.) Taub.) is a promising  crop for cultivation  in the south of Russia. In 2018, phytosanitary examinations of clusterbean fields (13 collection accessions) were conducted in five VIR branches (Krasnodar Territory, Dagestan,  Astrakhan and Volgograd Regions). At all points,  several types of leaf spots were observed on clusterbean leaves and symptoms of plant damage by fungi of the genus  Alternaria Nees prevailed.  Using microbiological  methods and  Next-Generation Sequencing (NGS) of the  nuclear  ribosomal internal  transcribed spacer  two (ITS2), the  species  composition of micromycetes was identified.  It was found  that the  micromycetes Alternaria spp. in different  ecological  and  geographical conditions of the  south  of Russia cause two main types of leaf spots: the typical (beige and brown round spots, usually accompanied by concentric zonality) and brown  spot (small brown  bulging  merging spots). Overwhelmingly  the damage to leaf tissues is caused  by the fungus  A. tenuissima (Nees & T. Nees : Fr.) Wiltshire. A quite  numerous accompanying mycoflora (first of all, fungi of the genus  Fusarium Link) was also detected. A. cyamopsidis Rangaswami & A.V. Rao, one of the most  harmful guar pathogens in the countries  where the main acreage is located  (India, Pakistan, USA), was not found on clusterbean fields in Russia. The accessions  of clusterbean differ in degree of damage by A. tenuissima that causes Alternaria leaf blight. Differential interaction of parasite  and plant  host was revealed.  Therefore, to prevent epiphytotics, varieties protected by non-identical resistance genes  should  be grown.  At all VIR branches, accessions  k-52568 (Argentina) and k-52569 (Pakistan) were weakly damaged by Alternaria leaf blight, and some  accessions  were resistant only in the environmental conditions of one or two experimental stations. The accessions  studied were heterogeneous  in pathogen resistance,  which  allows selecting  disease-resistant lines from most  of the  collection  accessions.  Thus, in various VIR branches, plants  without symptoms of disease  were selected from accessions  k-52571, k-52573 and k-52580, and seeds were collected to create new donors of disease resistance.